New records of Pimelodella (Siluriformes, Heptapteridae) from Colombia for the Amazon River basin, and redescription of P. serrata - Cortés-Hernández, Miguel Ángel; Méndez-López, Alejandro; Donascimiento, Carlos (Zootaxa, 2023)
We recorded Pimelodella bockmanni and P. serrata for the first time for Colombia, based on specimens collected in tributaries from the main channel of the Amazonas River, in the so-called Trapecio Amazónico, in the southernmost region of this country. We also present morphometric, meristic, and osteological data of the examined material, and provide a complementary morphological description of the poorly known P. serrata, a species known only from the Madeira River drainage in Bolivia and Brazil.